Methodological Principles of Investigating Ukrainian Phraseologisms in Media Discourse - Князь, Тетяна Миколаївна (Київський національний університет імені Тараса Шевченка, 2020)
The article deals with theoretical grounds of lingvo-pragmatic, functional, structural and semantic methods of research, which are used for analyzing phraseological units (PhU) of the Ukrainian language in media discourse. The verbal representation is the most powerful channel for information dissemination. That is why such important issues as the semantic and functional features of lexical, phraseological units of media discourse remain relevant. The clarification of the main methodological principles of studying the peculiarities of functioning the phraseology in the Ukrainian media discourse is the purpose of the proposed work. The object of research is the lingvo-pragmatic, structural and semantic features of phraseologisms’ functioning in the Ukrainian media discourse. Different types of structural and semantic transformations of phraseological units have been analyzed in the article. The transformed phraseologisms in media discourse demonstrate the dynamics of evaluative, ideological and cultural perception of reality. The realization of the pragmatic possibilities of “contracted” phraseological units happens due to the context or situation, the intentions of the speaker, as well as the linguistic and cultural competence of the communicator. Phraseological units play a special role in the process of communication, the pragmatic value of which lies in the ability to influence the addressee in a particular communicative situation. The phraseologisms of the Ukrainian language perform a variety of functions in the media discourse: nominative, evaluative, emotionally expressive, pragmatic, the function of characterizing the social status of social and political figures etc.

У статті подано огляд теоретичних засад лінгвопрагматичного, функціонального, структурно-семантичного методів дослідження фразеологізмів української мови в медійному дискурсі. Вербальна репрезентація є найпотужнішим каналом поширення інформації, саме тому актуальними залишаються такі важливі питання, як змістові та функціональні особливості лексичних, фразеологічних одиниць (ФО) медійного дискурсу. З’ясування основних методологічних засад дослідження особливостей функціонування фразеологізмів української мови в медійному дискурсі становить мету пропонованої роботи. Об’єктом дослідження є лінгвопрагматичні, структурно-семантичні особливості функціонування фразеологізмів української мови в медійному дискурсі. Розглянуто різні види структурно-семантичних трансформацій фразеологізмів. Трансформовані фразеологізми в медійному дискурсі демонструють динаміку оцінного, ідеологічного й культурного сприйняття дійсності. Реалізація прагматичних можливостей усічених фразеологізмів відбувається завдяки контексту чи ситуації, інтенцій мовця, а також з урахуванням мовної і культурної компетентності комуніканта. Фразеологізми відіграють особливу роль у процесі комунікації, прагматична цінність яких полягає в здатності вплинути на адресата в певній комунікативній ситуації. Фразеологізми української мови виконують у медійному дискурсі найрізноманітніші функції: номінативну, оцінну, емоційно-експресивну, прагматичну, функцію характеристики соціального стану суспільно-політичних діячів тощо.
Методологічні засади дослідження фразеологізмів української мови в медійному дискурсі
Keywords: media discourse; phraseological unit (PhU); transformation; lingvo-pragmatics; медійний дискурс; фразеологічна одиниця; трансформація; лінгвопрагматика